2021
DOI: 10.1186/s40792-021-01118-6
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of surgical treatment in patients with anorectal fistula cancer

Abstract: Background No standard treatment for anorectal fistula cancer, such as multidisciplinary therapy, has been established due to the rarity of the disease. Herein, we investigated patients with cancer associated with anorectal fistula who underwent surgery to clarify the clinicopathological characteristics and to propose future perspectives for treatment strategies. Case presentation Seven patients with cancer associated with anorectal fistula who und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 15 publications
(20 reference statements)
0
5
0
Order By: Relevance
“…In our patient, the fistula had been present for 4 years and there was no tumor present in the rectal mucosa. The authors of other studies in the literature have reported a varied time period between the onset of a fistula and its presentation as a malignant lesion (Table 1) [4][5][6][7][8][9][10][11].…”
Section: Discussionmentioning
confidence: 99%
“…In our patient, the fistula had been present for 4 years and there was no tumor present in the rectal mucosa. The authors of other studies in the literature have reported a varied time period between the onset of a fistula and its presentation as a malignant lesion (Table 1) [4][5][6][7][8][9][10][11].…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, this is the first report of implantation metastasis to an anal fistula after neoadjuvant therapy for rectal cancer in a patient without a history of anal fistula. Persistent anal fistulas with recurrent inflammation are known risk factors for primary cancer [ 13 ]. Furthermore, when colorectal cancer spreads to the anal fistula, cancer cells shedding into the intestinal lumen are implanted in the injured mucosa [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Of the three patients that underwent preoperative HRCT, two were successful in downstaging their tumors and all three achieved R0 resection. 30 Few reviews looking at outcomes on treatment provide information on whether immunosuppressant medications were continued during treatment. In one case report, the treating group continued the patient's TNF-α inhibitor through neoadjuvant therapy before ultimately stopping the medication prior to undergoing APR for mucinous adenocarcinoma.…”
Section: Treatmentmentioning
confidence: 99%
“…10 Similarly, a study evaluating surgical outcomes at a single institution in patients undergoing oncologic resection of FAAC noted that the use of a preoperative hyperthermochemoradiotherapy (HRCT) regimen was effective in downstaging tumors and may have played a role in successful R0 resection. 30 This regimen consisted of 50 Gy over daily 2 Gy fractions on 5 consecutive days per week. Capecitabine was given daily on radiation days for the 5 weeks of treatment.…”
Section: Treatmentmentioning
confidence: 99%
See 1 more Smart Citation